1991
DOI: 10.1001/archopht.1991.01080060076029
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Avascular Zone Diameter and Sickle Cell Disease

Abstract: background/aims To assess foveal avascular zone (FAZ) morphology and parafoveal capillary perfusion in patients with various stages of sickle cell retinopathy (SCR) using optical coherence tomography angiography (OCT-A). Methods This is a multi-institutional retrospective study of patients with various stages of SCR compared with healthy controls. Parafoveal OCT-A images obtained using a commercial spectral domain-OCT system were reviewed. Foveal-centred 3×3 mm full vascular slab OCT-As were used for image pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…8 The FAZ is enlarged in patients with sickle cell disease. 9 In addition, retinal vascular changes around the FAZ also occur early in diabetes mellitus with capillary dropout occurring even before the onset of retinopathy, 10,11 leading to a significant increase in the size of the FAZ. Furthermore, FAZ size is correlated with visual acuity in patients with diabetic retinopathy, 12 suggesting that assessment of the FAZ could be a useful biomarker for studying diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 The FAZ is enlarged in patients with sickle cell disease. 9 In addition, retinal vascular changes around the FAZ also occur early in diabetes mellitus with capillary dropout occurring even before the onset of retinopathy, 10,11 leading to a significant increase in the size of the FAZ. Furthermore, FAZ size is correlated with visual acuity in patients with diabetic retinopathy, 12 suggesting that assessment of the FAZ could be a useful biomarker for studying diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 FAZ borders are defined from the perifoveal capillary arcade, which consists of a ring of interconnected capillaries, formed by the superficial and deep vascular plexuses at the margin of the fovea. 3,7 The fovea centralis of the human provides high-resolution vision, and significant capillary dropout from this region, due to several retinal vascular diseases [8][9][10] , may cause severe visual loss. For this reason the perifoveal capillary network and FAZ have been studied in vitro and in vivo, using various methods, including histological techniques, high contrast entoptic view, fluorescein angiography (FA), and high-resolution imaging tools, such as adaptive optics and confocal scanning laser ophthalmoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The mean FAZ diameter was determined to be 0.56 mm by the trypsin digestion method [9], and 0.25 mm [10] or 2.04° [11] by entoptic methods. Using fluorescein angiography, the mean FAZ diameter was (in disk diameter) 0.32 [1], 0.34 [12], (in mm) 0.20 [10], 0.53 [13], 0.61 [4,13], 0.73 [3], while the mean FAZ area was 0.231 [14] and 0.35 mm2 [3]. Bird and Weale [10] initially demonstrated that blood vessels were common in the center of the fo vea.…”
Section: Discussionmentioning
confidence: 99%
“…This zone (FAZ) is polygonal in contour and its size reflects the microcapillary foveal circulation. The FAZ is small in retinopathy of prematurity [1] and posterior microphthalmos [2], while it is enlarged in certain vaso-occlusive diseases, such as diabetic retinopathy [3], sickle cell retinopathy [4,5], retinal branch vein occlusions and talc retinopathy [6]. The present study is aimed at measuring the area of the FAZ and analyzing the juxtafoveolar microaneurysmal distribution in IJFT.…”
Section: Introductionmentioning
confidence: 99%